Merdeka Belajar: Studi Kasus Kampus Mengajar Angkatan 3 di Sekolah Dasar - Yetni Marlina; Rahmat Muhdar (Peneliti.net, 2022)
Merdeka Learning is an idea launched by Nadiem Makarim who is the minister of Education and Culture to produce superior Human Resources (HR) by prioritizing character education. However, the Teaching Campus Program in schools is an effort to realize independent learning. So far, students and teachers have been teaching and learning to get high scores in exams so that learning is monotonous and does not hone students' skills at the elementary, secondary and tertiary education levels. As a result, the quality of graduates does not yet have the competencies needed by the world of work. The government is trying to overcome this problem through the Freedom to Learn policy. One of the Merdeka Learning programs for students is the Teaching Campus by involving students to help schools carry out fun teaching and learning activities, especially during the COVID-19 pandemic. This case study research was conducted at SDN 14 Kota Ternate through observation, interviews and document analysis. The results showed that the Teaching Campus program by sending students as agents of change to schools has helped the implementation of teaching and learning activities. Students, teachers and students are very enthusiastic despite facing various challenges. However, teachers have not been fully involved in the activities carried out by students during the program so that students doubt that there will be any sustainable changes in teaching and learning activities after the Campus Teaching program batch 3 ends. Thus, the 12-week Teaching Campus program is deemed insufficient to make significant changes to schools to create independent students and teachers.